A Fuzzy AHP–MARCOS Integrated Model for Cost Control Strategy Selection in Upstream Oil Operations - Ming Zhu; Ming Kuang; Meng Zhao; Xiang Wang (Decision Making: Applications in Management and Engineering, 2024)
International oil companies (IOCs) are under growing pressure to control costs amid increasing operational complexity and market volatility. This paper presents a structured model to help identify the most effective cost control strategies for the upstream segment. This approach integrates the Fuzzy Analytic Hierarchy Process (FAHP) and the Measurement of Alternatives and Ranking according to the Compromise Solution (MARCOS) to evaluate the relative importance of various criteria and prioritize alternatives based on these weighted factors, respectively. This integrated approach ensures a balanced consideration of expert insights and quantitative assessment under uncertain conditions. The results demonstrated that alternative A7 (Optimization of Supply Chain and Procurement) was the best-ranked alternative in the final ranking, while A5 (Integrated Planning of Drilling and Production Activities) ranks lowest. On the other hand, criterion C1 exerted the largest influence with the highest weight, followed by C2, C4, and C3, with C5 receiving the least significance. The results have shown that the developed model is highly applicable and can be extended to similar decision-making problems.